Development of a low-cost controller for the 3-axis computer numerically-controlled (CNC) plasma cutting machine - Liza, Fred P. (Animo Repository, 2015)
The Metals Industry Research and Development Center (MIRDC) designed and developed a 3-Axis computer numerically-controlled (CNC) plasma cutting machine for the local metahvorking industry. This CNC machine was dubbed as 'Plasmanoy∗ - short for 'Plasma ng Pinoy\ The said equipment is capable of cutting steel and other metals with a plasma torch. It uses high-Temperature plasma to melt the metal being cut. To produce precise and clean sharp cuts, computer control was introduced. However, the automation cost is quite expensive. With that, this study presents the development of a low-cost controller for the 3-Axis CNC plasma cutting machine. The developed controller is capable of digitally-controlling the mechanical motion of the three (3) axes (X, Y and Z) and the plasma generator. For the toolpath generation and post-processing, TAP extension file format was used.